Representation of differences in Brazilian journalistic discourse - Resende, Fernando (Brazilian journalism research, 2015)
Considering the technological advance, which enhances the production of mediatic discourses, and the notion of a libidinal power installed in our globalized societies, reflecting upon representation of differences seems to be a major issue. This essay discusses the production of journalistic discourses from an epistemological perspective. The field of media is taken as constituted by a triple component – discourse/narrative/machines – and we suggest that this triad has proved to be incomplete: discourse and narrative, once they really are vertexes of the triangle, are absences. Two journalistic-documentary productions – which intend to represent life in the slums of Brazil – are compared in order to reflect upon representation of differences in Brazilian journalistic discourse. In view of the up-to-date polarization and pulverization of discourses, we suggest that in the perspective of the journalistic discourse, one can only speak about alterity if one tries to comprehend the ways news is staged.